Protein cross-linking in food - Juliet A Gerrard; Meade SJ; Miller AG; Brown PK; Suhaimi Md. Yasir; Sutton KH; Newberry MP (2005)
The aims of this paper are (1) to probe the relationship betweenmolecular structure and protein cross-linking ability for a range of small mol-ecules; (2) to establish whether this relationship holds within a food matrix;and (3) to test the impact of Maillard cross-linking on food functionality, par-ticularly texture, in wheat- and soy-based food systems. A variety of moleculeswere obtained, either commercially or via organic synthesis. Cross-linkingability was tested using our standard model system, employing ribonuclease Aand analyzing the results by SDS-PAGE. Molecules of varying reactivity weretested in wheat- and soy-based products, and the changes in functionality werecorrelated with changes in protein cross-linking. No simple relationship wasfound between molecular structure and ability to cross-link ribonuclease. Onlythe most reactive reagents were able to cross-link within the food matrix.Nevertheless, a low degree of cross-linking was shown to have significant con-sequences on the properties of wheat- and soy-based foods, suggesting that theMaillard reaction may represent a means to control food texture.